La escultura neo-colombina: intervenciones artísticas y fotografías del alzheimer de oro - Enderica Chávez, Cristina Elizabeth (Machala, 2021)
The cultural, documentary and artistic heritage of the Province of El Oro is in an extremely precarious and alarming state, this added to the scarce interest that the population of El Oro has in knowing its aboriginal culture and its identity value, has motivated the realization of the present work with the purpose of creating an artistic contribution that recalls the ancestral imaginary of the people. In Machala and in the other cantons of the province there have been a series of findings of pre-Columbian objects that, despite their great cultural and historical importance, have been little or nothing valued by local authorities and the community. For this reason, it has been considered to approach this problem from an artistic paradigm, retaking the work of our aborigines through the artisan practice of sculpture and its modeling technique, recreating Neo-Columbian statuettes with the jambelí aesthetics and other contextual symbolic elements that turn them into new objects of artistic identity. The technique of modeling, being one of the most primitive communicative activities of mankind, also needs to make use of other expressions of modern art to correctly convey the artist's intentions. Within these techniques and for our purposes, photography and artistic intervention in public spaces play an important role in re-establishing the link between community and artistic dynamics within the daily context. In addition to these additional resources to the artistic object, it is also conceived to devise the formal aspect of the work with a redesign of the neo-figurine Jambelí, using non-traditional materials such as plasticine, fiberglass, resin, silicone, air-drying pastes, aerosols, etc. in methodological processes such as casting and reproduction of the pieces from a mold. On the other hand, the theoretical foundations of the work are based on the Relational Aesthetics described by Bourriaud and Carlos Rojas' Cannibal Aesthetics, which, based on the appropriation of cultural symbols and physical/virtual and inclusive public spaces, invite the reflection of the passive individual in art and transform him/her into an active receiver of the new aesthetic experiences. In addition to these two main theoreticians, other conceptual authors, plastic referents and, above all, the scarce but important contributions of historical-archaeological research that have taken place in the province are cited. In summary, the project aims at the following: - To elaborate small-format sculptures with theoretical-plastic foundations of pre-Columbian aesthetics and, through artistic intervention in the public space, to disseminate the results to promote in the community an appreciation of ancestral memory and local identity. Contemporary art must then become an innovative tool that makes possible other realities or aesthetic appreciations as a result of a contextual problem. In this way, artistic practice responds to the need to encourage a reconstruction of socio-cultural, ethical and aesthetic values, pretending that subjects isolated or alien to these expressions, are activated and create new bonds of belonging and appreciation through art. The neo-Columbian sculpture, in its attentive intervention and photographic diffusion, will be the nexus that strengthens these ties in the artistic paradigm.
El patrimonio cultural, documental y artístico de la Provincia de El Oro se encuentra en un estado extremadamente precario y alarmante, esto sumado al escaso interés que tiene la población orense por conocer acerca de su cultura aborigen y su valor identitario, ha motivado la realización del presente trabajo con la finalidad de crear un aporte artístico que rememora el imaginario ancestral de la localidad. En Machala y los demás cantones de la provincia, se ha evidenciado una serie de hallazgos de objetos precolombinos que, a pesar de su gran importancia cultural e histórica, han sido poco o nada valorados por las autoridades locales y la comunidad. Se ha considerado entonces abordar esta problemática desde un paradigma artístico, retomando el quehacer de nuestros aborígenes mediante la práctica artesanal de la escultura y su técnica del modelado, al recrear estatuillas neo-colombinas con la estética Jambelí y otros elementos simbólicos contextuales que las convierten en nuevos objetos artísticos identitarios. La técnica del modelado, siendo una de las actividades comunicativas más primitivas de la humanidad, precisa valerse también de otras expresiones del arte moderno para transmitir correctamente las intenciones del artista. Dentro de estas técnicas y para nuestros fines está la fotografía y la intervención artística en espacios públicos que juegan un papel importante para re-establecer el vínculo entre comunidad y la dinámica artística dentro del contexto cotidiano. Además de estos recursos adicionales al objeto artístico también se concibe idear el aspecto formal de la obra con un rediseño de la neo-figurina Jambelí, usando materiales no tradicionales como la plasticera, fibra de vidrio, resina, silicona, pastas que se secan al aire, aerosoles, etc. en procesos metodológicos como la fundición y reproducción de las piezas a partir de un molde. Por otra parte, los fundamentos teóricos de la obra se sustentan en la Estética Relacional descrita por Bourriaud y Estéticas Caníbales de Carlos Rojas, mismos que, a partir de la apropiación de símbolos culturales y espacios públicos físicos/virtuales e inclusivos, invitan a la reflexión del individuo pasivo en el arte y lo transforman en receptor activo de las nuevas experiencias estéticas. Además de estos dos principales teóricos, se cita a otros autores conceptuales, referentes plásticos y sobre todo a los escasos pero importantes aportes de las investigaciones histórico-arqueológicas que se han dado en la provincia. En resumen, el proyecto tiene como objetivo lo siguiente: - Elaborar esculturas de pequeño formato con fundamentos teórico-plásticos de la estética precolombina y, mediante la intervención artística en el espacio público, difundir los resultados para promover en la comunidad una apreciación sobre la memoria ancestral e identidad local. El arte contemporáneo entonces debe convertirse en una herramienta innovadora que posibilite otras realidades o apreciaciones estéticas a raíz de una problemática contextual. De este modo la práctica artística responde a la necesidad de alentar una reconstrucción de los valores socio-culturales, éticos y estéticos, pretendiendo que sujetos aislados o ajenos a estas expresiones, se activen y creen nuevos lazos de pertenencia y apreciación a través del arte. La escultura neo-colombina en su atinada intervención y difusión fotográfica, será el nexo que fortalezca estos lazos en el paradigma artístico.
Keywords: ESCULTURA; FOTOGRAFIA; INTERVENCION ARTISTICA; CULTURA JAMBELI; MEMORIA ANCESTRAL; NEO-COLOMBINO; ESTETICA RELACIONAL